Arnica Montana L. Supercritical Extraction Optimization for Antibiotic and Anticancer Activity - Žitek, Taja; Postružnik, Vesna; Knez, Željko; Golle, Andrej; Dariš, Barbara; Knez Marevci, Maša (Frontiers in Bioengineering and Biotechnology, 2022)
Arnica montana L. flower heads are known for their antioxidant, antimicrobial, and anticancer activity. The aim of this work was to optimize the process of supercritical CO2 extraction, to achieve high extraction yield and high content of biologically active components, and to confirm the antimicrobial and anticancer activity of the extract. The influence of pressure and temperature on the total phenolic content, antioxidant activity, and proanthocyanidin content was evaluated. The pressure and temperature were found to be interdependent. A temperature of 60°C and a pressure of 30 MPa resulted in a high extraction yield, antioxidant activity and phenolic content. The content of proanthocyanidins was highest at a pressure between 18 and 24 MPa. The extracts inhibited three different microorganisms successfully; Staphylococcus aureus, Escherichia coli and Candida albicans, at concentrations ranging from 0.1 to 5.16 mg/ml and showed anticancer activity decrease up to 85% at a concentration of 0.5 mg/ml.